Penyuluhan Kesehatan tentang Pentingnya Gizi untuk Ibu Menyusui di Desa Kaliwadas Kecamatan Bumiayu - Siti Fatimah; Esti Nur Janah; Linda Febri Oktaviana; Riska Meilina (STIKes Ibnu Sina Ajibarang, 2024)
An important indicator of health status is the nutritional needs of breastfeeding mothers, and currently the nutritional needs of mothers after giving birth are higher than during pregnancy. The thing that needs to be considered during the golden period for toddlers for the development and growth process of toddlers is the provision of balanced nutrition for breastfeeding mothers. Breastfeeding is the most important source of nutrition for the healthy growth and development of babies, and has biological and psychological impacts on the health of mothers and children. Breast milk is the perfect food or nutrition for babies. In the first six months of life, breast milk is the most complete source of nutrition to support the baby's growth and development. This Community Service Activity was carried out at Dk. Congkar 1/1 Kaliwadas Village, Bumiayu District. The aim of this Health Education Activity is to increase mothers' knowledge about the importance of nutrition for breastfeeding mothers. This Community Service activity is carried out using lecture, discussion and question and answer methods using posters and modules. It is hoped that in the future health workers can strive for innovative methods to increase maternal knowledge.